Fenomena-Fenomena Paradigmatik Dunia Pengadilan di Indonesia (Telaah Kritis terhadap Putusan Sengketa Konsumen) - artidjo alkostar (Fakultas Hukum Universitas Islam Indonesia, 2004)
In issuing the court in Indonesia, the independence of the court is often interfered by power interest with many various background. Today, after the act No. 4, 2004 on the Judicial Affairs and the act No.5, 2004 on The Supreme Court issued, the effort of interference are probably not repeated. It is caused that judicature institution both in organization, administration and financial are not directedbyDepartment of Administration, but it applies the one roofpolicy underthe Supreme Court. The significant change paradigmatically would strengthen the autonomy, transparence, and responsibility for every judge in deciding the case in the level of any judicature (Human RightsJudicature,Trade Judicature, Convptiori Judicature and the Commission of Consumers ConflictSolution).